2018
DOI: 10.15252/embj.201899071
|View full text |Cite
|
Sign up to set email alerts
|

CPEB 2‐dependent translation of long 3′‐ UTR Ucp1 mRNA promotes thermogenesis in brown adipose tissue

Abstract: Expression of mitochondrial proton transporter uncoupling protein 1 (UCP1) in brown adipose tissue (BAT) is essential for mammalian thermogenesis. While human UCP1 mRNA exists in a long form only, alternative polyadenylation creates two different isoforms in mice with 10% of UCP1 mRNA found in the long form (Ucp1L) and ~90% in the short form (Ucp1S). We generated a mouse model expressing only Ucp1S and found that it showed impaired thermogenesis due to a 60% drop in UCP1 protein levels, suggesting that Ucp1L i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 65 publications
3
19
0
Order By: Relevance
“…We previously found that loss of CPEB2 in the dorsal motor nucleus of the vagus neurons leads to translational upregulation of choline acetyltransferase, thereby increasing pulmonary acetylcholine level to induce bronchoconstriction-associated apnea in neonatal pups [23]. However, surviving CPEB2-KO mice can live for at least 1 year without obvious physical problems except for reduced thermogenesis in brown adipose tissues [27]. To investigate whether the abnormal breathing patterns in neonatal CPEB2-KO mice persist into adulthood, we used a non-invasive whole-body plethysmography (WBP) to analyze their breathing patterns.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously found that loss of CPEB2 in the dorsal motor nucleus of the vagus neurons leads to translational upregulation of choline acetyltransferase, thereby increasing pulmonary acetylcholine level to induce bronchoconstriction-associated apnea in neonatal pups [23]. However, surviving CPEB2-KO mice can live for at least 1 year without obvious physical problems except for reduced thermogenesis in brown adipose tissues [27]. To investigate whether the abnormal breathing patterns in neonatal CPEB2-KO mice persist into adulthood, we used a non-invasive whole-body plethysmography (WBP) to analyze their breathing patterns.…”
Section: Resultsmentioning
confidence: 99%
“…CPEB2 can bind to eukaryotic translation elongation factor 2 (eEF2) and downregulate eEF2's GTPase activity to impede translation of hypoxia-inducible factor 1α mRNA [24,25]. Similar to other CPEB family proteins, CPEB2 can also promote translation of some of its target mRNAs [26,27]. Previously, we found that CPEB2-KO neonatal mice showed aberrant respiration with frequent apnea and died mostly within 3 days after birth.…”
Section: Introductionmentioning
confidence: 99%
“…The poly(A) site of Ucp1 in koala and gray short-tailed opossum in Marsupialia is located at 1,389 and 2,074 bp downstream of the stop codon, respectively, implying Ucp1 in both species may be subjected to more complex posttranscriptional regulation. Other than the 3′-UTRs of rat Ucp1S , mouse Ucp1S and Ucp1L , and human UCP1 having been confirmed by cDNA sequencing ( 17 , 18 , 21 ), the actual usage and preference of the two putative polyadenylation sites in other species require further investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Northern blot analysis revealed two Ucp1 transcripts of ~1.5 and 1.9 kb (hereafter called Ucp1S and Ucp1L ) in mouse and rat BAT ( 15 , 16 ). The transcripts result from an alternative use of the poly(A) signal to yield 3′-UTRs of 78 and 485 bp in mice, respectively ( 21 ) ( Figure 1B ). By contrast, only the distal poly(A) signal is used to generate Ucp1L in rabbit BAT ( 20 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation